2020
DOI: 10.28991/scimedj-2020-02-si-4
|View full text |Cite
|
Sign up to set email alerts
|

A Mathematical Study of a Generalized SEIR Model of COVID-19

Abstract: In this work (Part I), we reinvestigate the study of the stability of the Covid-19 mathematical model constructed by Shah et al. (2020) [1]. In their paper, the transmission of the virus under different control strategies is modeled thanks to a generalized SEIR model. This model is characterized by a five dimensional nonlinear dynamical system, where the basic reproduction number can be established by using the next generation matrix method. In this work (Part I), it is established that the disease free equili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…The results of the excision theorem of the dihedral cohomology equipped with the results of Intissar (2020) and Kostikov and Romanenkov (2020). Also, our results can introduce this application in a new form.…”
Section: Public Interest Statementmentioning
confidence: 74%
See 1 more Smart Citation
“…The results of the excision theorem of the dihedral cohomology equipped with the results of Intissar (2020) and Kostikov and Romanenkov (2020). Also, our results can introduce this application in a new form.…”
Section: Public Interest Statementmentioning
confidence: 74%
“…We discussed and proved some theorems in the cyclic and dihedral cohomology of an associative algebra and we studied a new form and new theorems in this area. We can apply this theorem in the operator algebra in the next work and apply this result in our life working as by Intissar (2020) to improve results. Our result can be equipped with the result by Kostikov and Romanenkov (2020) and can improve it by using our result.…”
Section: Resultsmentioning
confidence: 99%
“…The case studies for COVID-19 can be found in [4][5][6][7][8][9][10][11][12][13][14][15][16], especially for Wuhan, China [4][5][6][7][8]. For example, Li et al (2020) [4] described the characteristic of positive cases, the distributions of epidemiological time delay, the disease doubling time, and the breeding number, based on the data of Wuhan.…”
Section: Related Work: Modeling the Diseasementioning
confidence: 99%
“…There are case studies for COVID-19 [4][5][6][7][8][9][10][11][12][13][14][15][16], especially for Wuhan, China [4][5][6][7][8]. Various models for the disease have been studied in 2020, including mathematical models [7][8][9][10][11][12][13][14][15][16][17][18][19], statistical modeling [20][21][22], and artificial intelligence (AI) models [15,[22][23][24]. Details of the studies are presented in section 2.…”
mentioning
confidence: 99%
“…Studies have been performed for modeling the physical transportation of COVID-19 in the air [6] , [7] . In [8] , the stability of the transmission model of COVID-19 that was developed based on the SEIR model was investigated under different control strategies. In [9] , The transmission of the airborne germ of COVID-19 was provided from a physics view based on fluid dynamics analysis methodology.…”
Section: Introductionmentioning
confidence: 99%